On a short handle? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
A recent study, by FAO and IFAD, on the widespread use of short-handled hoes emphasised that many women complained about frequent pain and fatigue. 'Without doubt,' the report says, 'short-handled weeding hoes have the advantage of allowing the...